2015
DOI: 10.3109/00498254.2015.1077403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based inactivation of cytochrome P450 2B6 by isopsoralen

Abstract: 1. Isopsoralen (IPRN) is a major component in many traditional medicinal herbs widely used in Asian countries. The objective of the present study was to investigate the inhibitory effect of IPRN on cytochrome P450 2B6 (CYP2B6) and the mechanism involved in the enzyme inactivation. 2. Pre-incubation of CYP2B6 with IPRN resulted in a time- and concentration-dependent enzyme activity loss. The values of K(I) and k(inact) were found to be 7.89 μM and 0.067 min(-1), respectively. Ticlopidine exhibited protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The inactivating effect is not produced by psoralen itself, rather its furan epoxy derivatives formed by epoxidation, or γ-ketonene formed by direct oxidation. In addition, the mechanism of inactivation was previously reported [ 29 , 30 ]. In addition, previous studies have chosen the CYP2B6 probe drug bupropion as a metabolic substrate and demonstrated that clopidogrel strongly inhibits recombinant human CYP2B6 enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivating effect is not produced by psoralen itself, rather its furan epoxy derivatives formed by epoxidation, or γ-ketonene formed by direct oxidation. In addition, the mechanism of inactivation was previously reported [ 29 , 30 ]. In addition, previous studies have chosen the CYP2B6 probe drug bupropion as a metabolic substrate and demonstrated that clopidogrel strongly inhibits recombinant human CYP2B6 enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…A furan ring double bond is oxidized to produce a reactive furanoepoxide or γ-ketoenal intermediate, resulting in irreversible inhibition of CYP450s. A number of active furan epoxides have been demonstrated to cause hepatotoxicity ( Mays et al, 1990 ; Koenigs and Trager, 1998a ; Koenigs and Trager, 1998b ; Wang et al, 2012 ; Lu et al, 2016 ). Song et al found that psoralen may induce liver injury in rats through the cytochrome P450 metabolic pathway of xenobiotics, among which Akr7a3, Gstm1, Cyp1a2, and Cyp1a1 are important genes in hepatotoxicity, and the endoplasmic reticulum is the principal target subcellular structure.…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Approximately, CYP2B6 accounts for 2%-10% of total hepatic P450 content, and it metabolizes 3%-12% of all drugs (Zanger et al, 2007;Wang and Tompkins, 2008). So far, several CYP2B6 TDI inhibitors have been reported including isopsoralen (Lu et al, 2016), isoimperatorin (Cao et al, 2015), selegiline (Sridar et al, 2012), ticlopidine, and clopidogrel (Richter et al, 2004). Compared with those known TDI inhibitors, PBD is highly unusual given that inactivation of CYP2B6 does not require NADPH-dependent bioactivation.…”
Section: Namementioning
confidence: 99%